Maya kingship: rupture and transformation from Classic to Postclassic times - Okoshi, Tsubasa; Chase, Arlen Frank; Nondédéo, Philippe; Arnauld, Marie-Charlotte; Chase, Diane Elizabeth Zaino (Maya Studies, 2021)
Examining changes to the institution of divine kingship from 750 to 950 CE in the Maya lowland cities, this volume presents a new way of studying the collapse of that civilization and the transformation of political systems between the Terminal Classic and Postclassic Periods.